2009
DOI: 10.1111/j.1749-4486.2008.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary audit of clinical coding accuracy in otolaryngology: financial, managerial and clinical governance considerations under payment‐by‐results

Abstract: This large audit of otolaryngology practice identifies a large degree of error in coding on discharge. This leads to significant loss of departmental revenue, and given that the same data is used for benchmarking and for making decisions about resource allocation, it distorts the picture of clinical practice. These can be rectified through implementing a cost-effective clinician-coder double-reading multidisciplinary team as part of a data-assurance clinical governance framework which we recommend should be es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 8 publications
0
56
0
Order By: Relevance
“…In our dataset, these were the causes for three of the errors. In theory, these could be reduced by training and increasing clinical involvement (see [8] for a discussion). The second source of error is in the mismatch which occurs in using administrative data for clinical purposes.…”
Section: Discussionmentioning
confidence: 98%
“…In our dataset, these were the causes for three of the errors. In theory, these could be reduced by training and increasing clinical involvement (see [8] for a discussion). The second source of error is in the mismatch which occurs in using administrative data for clinical purposes.…”
Section: Discussionmentioning
confidence: 98%
“…[13][14][15] A recent systematic review of discharge coding accuracy in the UK concluded that routinely collected data are sufficiently robust to support their use for research and managerial decision-making. 10 The richness of the data also makes it possible to develop coding frameworks and data quality criteria to identify hospitals with divergent coding practices by combining diagnosis, procedure, and administrative codes.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimates do not include GW diagnoses and costs from a number of other health services which provide sexual health screens in England, but for which no surveillance data are currently available 17. The HRG method has not been previously used to estimate costs of GWs in hospitals, and possible inclusion of unrelated operative codes and other errors of the nature found in a study of diagnoses and operative procedures for otolaryngology18 may have caused over- or under-estimation of hospital costs. Hospital costs may have been underestimated by exclusion of GW codes other than the primary diagnosis and of outpatient care.…”
Section: Discussionmentioning
confidence: 99%